The trend of development of domestic air travel market in the context of Ukraine’s accession to the Single European Sky - Корчак, Наталія Миколаївна; Капустинський, Олексій Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article considers the principle of air space freedom in regards to flights over the high seas, gives a clear differentiation between the Open Skies Treaty and the Open Skies Agreement. There has been made an attempt to give the authors’ own assessment of the main issues and prospects for the implementation of the transport strategy of Ukraine in the civil aviation in 2020. Also there have been covered specifics of the Ukrainian market of the air transportation development on the way to signing the Open Air Agreement.